The Role of Islamic Religious Education in The Development of Students Spirituality and Morality in The Digitalization Era: Case Study of Students at Universitas Pertiba Pangkalpinang - Efendi Sugianto (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Islamic Religious Education (PAI) plays a crucial role in fostering students' spirituality and morality in the digitalization era. This study focuses on students at Pertiba University Pangkalpinang, examining how rapid digitalization impacts their behavior and values. While digital media offers vast opportunities for information access, it also poses challenges to students’ spiritual and moral integrity. PAI in higher education serves as a guide to internalize religious values, helping students counter negative digital influences. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis with students enrolled in PAI courses. The findings indicate that PAI positively contributes to students’ spiritual and moral development. Students acknowledge that PAI provides essential insights into preserving religious values amidst the digital information flood. Furthermore, PAI enhances students' critical thinking in filtering information and promotes responsible digital media usage. The study concludes that PAI significantly shapes the spiritual and moral character of Pertiba University students, equipping them to navigate the challenges of the digital era. It recommends further development of PAI with approaches tailored to students’ needs and emphasizes the role of lecturers as moral role models on campus.